Peningkatkan Mutu Pendidikan Di Madrasah (Studi Kasus Pada Madrasah Tsanawiyah Salafiyah Prambontergayang Soko Tuban) - Zakiyah Kholidah (LPPM Institut Agama Islam Al-Hikmah Tuban, 2019)
Abstract, the focus of this research is describing the strategy of madrasah in developing islamic educational management quality at MTs Salafiyah Prambontergayang, Tuban, through input, process, and output. This research is a qualitative approach using a case study, data resources, data collection technique are in-depth interview, non-participant observation, and document study. The data collected interactively in accordance with Miles and Huberman model. Result of this research shows: Strategy of headmaster in developing quality of education at MTs Salafiyah Prambontergayang, Tuban are: effective communication and continuos coordination; self-management and entrepreneurship and participative-delegative leadership; academic achievement and nonacademic achievement.Keywords: Madrasah Headmaster, Management, Educational Quality.